Sperm aneuploidy and recurrent pregnancy loss: A systematic review and meta-analysis. Issue 1 (1st January 2020) - Pu, Yifu; Yang, Xiaoli; Guo, Yujin; Zhu, Xingwang; Yan, Lei; Lu, Shaoming
Abstract: Background and Objective:Studies have reported that the spouses of patients with recurrent miscarriage have a high rate of sperm aneuploidy, The types and the methods of determination of sperm aneuploidy are different. The correlation between the specific type of sperm aneuploidy and recurrent miscarriage is inconclusive.Here, we performed a systematic review and meta-analysis to investigate the rate of sperm aneploidy tested in FISH way in male partners of women with recurrent pregnancy loss (RPL group) and fertile male control groups. Methods:Cochrane, Embase, Web of Science, and PubMed databases and a manual search were done for observational research from inception till 23 May 2019.Pooled standard mean difference (SMD), odds ratios (ORs) and 95% confidence interval (CI) were used to describe effect sizes.This study was conducted according to MOOSE statement. Results:Overall, One study was included for qualitative analysis owing to a lack of standard deviation data, and nine studies were included for quantitative analysis.326 male partners of women with recurrent pregnancy loss and 124 fertile men were included in this study.The primary outcome was the rate of sperm aneuploidy. Pooled data from three studies with sufficient data suggested that male partners of women with a history of RPL had significantly higher rates of total sperm aneuploidy compared with the partners of fertile control women(SMD: 1.07, 95% CI: 0.39–1.75, P < 0.01). In the qualitative analysis, the RPL group had a greater percentage of sperm aneuploidy, Conclusions:Qualitative analysis and quantitative analysis suggested an association between total sperm aneuploidy and RPL. However, for some specific type of sperm aneuploidy, male partners of women with a history of RPL had similar rates as fertile men. Further studies are needed owing to the significant heterogeneity between studies and lack of prospective pregnancy outcome data.